Peningkatan Komunikasi Interpersonal melalui Bimbingan Kelompok Teknik Role Playing pada Siswa SMKN 1 Surabaya - Maghfira, Ervinda Rosana; Lathifah, Maghfirotul; Apriliyanti, Hidayatul; Alfachroini, Hilda Risma (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Interpersonal communication is an important thing that cannot be separated from the process of life both in the residential environment and the school environment. Low interpersonal communication will affect the difficulty in establishing relationships as social beings. This study is intended to improve interpersonal communication with group guidance using role-playing techniques. This study is a classroom action research using the purposive sampling method, the sample used was 35 students in class X PSPT 1. The focus of this study is on interpersonal communication of students at SMK N 1 Surabaya. Data collection through observation, interviews, and interpersonal communication scales, while data analysis uses graphic visual analysis techniques. The results of the study showed that before the service was given, there were 20% of students who had low interpersonal communication, 65.71% were moderate and 14.29% were high. After being given service intervention, there was an increase in the strength of interpersonal communication, this was evidenced by the results of the post-test at the end of the cycle, the number of students with low interpersonal communication decreased drastically to 2.86%, while students with moderate interpersonal communication increased to 37.14%, and the high category increased to 60%. Role-playing techniques have been proven effective in improving students' interpersonal communication skills, helping them interact better with peers, teachers, and the school environment